Voice to Sign Language Translator System - Wan, Terrence Lawai (Universiti Teknologi PETRONAS, 2007)
The process of learning the sign language may be cumbersome to some, and therefore, this project proposes a solution to this problem by providing a voice (English Language) to sign language translator system solution using Speech and image processing. Speech processing which includes Speech Recognition is the study of recognizing the words being spoken, regardless of whom the speaker is. This project uses template-based recognition as the main approach. In this approach, computer first needs to be trained with speech pattern based on some generic spectral parameter set. These spectral parameter set then will be stored as template inside the database. The system will perform the recognition process through matching the parameter set of the input speech with the stored template. Pattern recognition will be used for this project because it has the advantage of flexibility in terms of storage and matching process. In addition, its implementation is easier as compared to other methods. This paper discusses on the solution to the problem stated above, as well as the methodologies used to develop the system.